Prone positioning in acute respiratory distress syndrome after abdominal surgery: a multicenter retrospective study: SAPRONADONF (Study of Ards and PRONe position After abDOmiNal surgery in France) - Gaudry, Stéphane (Ann Intensive Care, 2017)
BACKGROUND: The recent demonstration of prone position’s strong benefit on patient survival has rendered proning a major therapeutic intervention in severe ARDS. Uncertainties remain as to whether or not ARDS patients in the postoperative period of abdominal surgery should be turned prone because of the risk of abdominal complications. Our aim was to investigate the prevalence of surgical complications between patients with and without prone position after abdominal surgery. METHODS: This study was a multicenter retrospective cohort of patients with ARDS in a context of recent abdominal surgery. Primary outcome was the number of patients who had at least one surgical complication that could be induced or worsened by prone position. Secondary outcomes included effects of prone position on oxygenation. Data from the prone group were compared with those from the supine group (not having undergone at least a prone position session). RESULTS: Among 98 patients included, 36 (37%) had at least one prone position session. The rate of surgical complications induced or worsened by prone position did not differ between prone and supine groups [respectively, 14 (39%) vs 27 (44%); p = 0.65]. After propensity score application, there was no significant difference between the two groups (OR 0.72 [0.26–2.02], p = 0.54). Revision surgery did not differ between the groups. The first prone session significantly increased PaO(2)/FiO(2) ratio from 95 ± 47 to 189 ± 92 mmHg, p < 0.0001. CONCLUSION: Prone position of ARDS patients after abdominal surgery was not associated with an increased rate of surgical complication. Intensivists should not refrain from proning these patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13613-017-0235-z) contains supplementary material, which is available to authorized users.